Molecular cloning of the bovine prolactin receptor and distribution of prolactin and growth hormone receptor transcripts in fetal and utero-placental tissues - Scott, P; Kessler, M A; Schuler, L A (Molecular and cellular endocrinology, 1992)
We have isolated a bovine prolactin (bPRL) receptor cDNA from an endometrial cDNA library, which predicts a 557 amino acid transmembrane protein similar to the long forms of other characterized prolactin receptors. The predicted cytoplasmic domain is slightly truncated primarily by a stop codon located 36 codons 5' from the stop utilized in the human hepatic transcript. When expressed in COS cells, this cDNA was shown to encode a protein which bound bovine placental lactogen (bPL) and bPRL with nearly equal affinity (KD for bPL, 2.03 x 10(-10) M; bPRL, 3.07 x 10(-10) M). Northern analysis demonstrated multiple transcripts, with maternal liver, corpus luteum, intestine, endometrium and fetal liver containing a major transcript of about 3.8 kb, and maternal corpus luteum and endometrium, a second sized transcript of apparently equal abundance of 4.4 kb. This difference did not appear to be within the coding region. Primer extension analysis of maternal hepatic and endometrial transcripts revealed considerable heterogeneity. Examination of the distribution of prolactin and growth hormone receptor transcripts at mid-pregnancy by semi-quantitative reverse transcriptase polymerase chain reaction showed that both are widespread in bovine fetal and placental tissues. This isolation of bovine prolactin receptor cDNA, and description of receptor distribution will facilitate study of the action of the placental and pituitary members of this gene family during pregnancy.